GERMINAÇÃO E PROPAGAÇÃO IN VITRO DE CEREJEIRA (Amburana acreana (Ducke) A.C. Smith - FABACEAE) - Paulo Cesar Poeta Fermino Junior; Jonny Everson Scherwinski-Pereira (Ciência Florestal, 2012)
Cerejeira (Amburana acreana) is a woody native tree species from south-western Amazon Region of a great importance and endangered. The propagation by tissue culture of this species is of a great importance because the difficulties of its seed collection. The purpose of this study was to evaluate the in vitro germination and to establish a protocol for in vitro multiplication and rooting. For in vitro germination, the salt concentrations of MS and WPM (Woody Plant Medium) were evaluated. For in vitro multiplication of shoots it was used nodal segments of in vitro seedlings. The propagation media were composed of WPM salts, supplemented with different BAP concentrations (0, 0.25, 0.5, 1.0, 2.0, 4.0, 8.0 mg.L-1) and 0.1 mg L-1 of NAA. The in vitro rooting was induced in half strength WPM salts, plus 0.2 mg L-1 activated charcoal and supplemented with different IBA concentrations (0, 0.5, 1.0, 2.0 mg.L- 1). The highest percentage of in vitro germination was obtained in the MS/2 medium. The formation of largest number of shoots occurred with 4.0 mg L-1 BAP. The formation of a greater number of roots occurred with 0.5 mg L-1 of IBA. The plantlets were air-conditioned in a greenhouse with 54% of survival rate. The in vitro propagation of Cerejeira is a viable technology for the production of seedlings in spite of the difficulties in the survival of plants in the greenhouse.